Modelling and experimental sutdies on water and solute dynamics in subsurface drained land: a review - Singh, Man; Bhattacharya, A K; Singh, A K; Singh, A (Journal of Agricultural Engineering, 2005)
Last 30 years of results on the application of simulation models with input from subsurface drained fields have been reviewed with special reference to desalinization and salinization with and without subsurface drainage; drainage effluent quality and space-time distribution of soil salinity and nitrogen losses via leaching and drainage effluent. Nutrient loss studies mostly considered leaching loss of nitrate N. Ammonium N loss was viewed to occur mainly through volatilization. India has a large coastal agricultural land with clayey soils, afflicted by salinity and sodicity. Such an environment precludes normal route of N transformation. As a result, there may be ammonium losses via mass flow, causing an under-utilization of N - fertilizer. The review establishes the need of conducting model studies supported by field experimental data, for developing best management strategies both on land reclamation through drainage and application of N - fertilizer.